2007
DOI: 10.1371/journal.pone.0000827
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Response to Shear Stress Critically Depends on Endothelial TRPV4 Expression

Abstract: BackgroundIn blood vessels, the endothelium is a crucial signal transduction interface in control of vascular tone and blood pressure to ensure energy and oxygen supply according to the organs' needs. In response to vasoactive factors and to shear stress elicited by blood flow, the endothelium secretes vasodilating or vasocontracting autacoids, which adjust the contractile state of the smooth muscle. In endothelial sensing of shear stress, the osmo- and mechanosensitive Ca2+-permeable TRPV4 channel has been pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
219
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(241 citation statements)
references
References 53 publications
19
219
0
3
Order By: Relevance
“…TRPC3-and TRPC6-induced Ca 2+ inflow underpin the stimulatory effect of VEGF on endothelial proliferation, migration and permeability [18,231,236] , while ATP exploits TRPC3 to activate NF-κB and increase vascular cell adhesion molecule-1 expression [237] . TRPC3-driven NO synthesis and vasore- TRPV1 TRPV2 TRPV3 TRPV4 TRPV5 TRPV6 PCa/PNa and conductance (pS) [202] 10, 35-80 1-3, NM 12, 172 6, 90 > 100, 75 > 100, 40-70 Human coronary artery ECs [300] (+RT-PCR, WB, IHC) Human pulmonary artery ECs [415] +(RT-PCR) +(RT-PCR) +(RT-PCR) Human pulmonary microvascular ECs +(RT-PCR) Human cerebral microvascular ECs [272] +(RT-PCR, IC) Human cerebral arterioles ECs [305] +(RT-PCR, IHC) Human dermal microvascular ECs [319] +(RT-PCR, WB) Breast cancer derived microvascular ECs [319] +(RT-PCR, WB) Human umbilical vein ECs [227,277,296,301] +(RT-PCR) +(WB, IHC) Mouse aortic ECs [280,285,299,306] +(WB) +(RT-PCR, WB, NM, IHC) Mouse pulmonary artery ECs [313] +(WB, IHC) Mouse mesenteric artery ECs [27,280,302] +(RT-PCR, WB, IC) +(RT-PCR, IC) Mouse cerebral microvascular ECs +(RT-PCR) +(RT-PCR, WB) +(RT-PCR) Mouse dermal microvascular ECs [307] +(RT-PCR, WB) Mouse carotid artery ECs [290,296] +(IHC) Rat mesenteric artery ECs [226,275,302] +(WB) +(WB, IC, IHC) Rat femoral artery ECs [312] +(RT-PCR, IC) Rat pulmonary artery ECs [303] +(WB, IHC) Rat renal artery ECs [303] +(IHC) Rat cardiac microvascular ECs [303,…”
Section: A Drop In Luminal Camentioning
confidence: 99%
See 2 more Smart Citations
“…TRPC3-and TRPC6-induced Ca 2+ inflow underpin the stimulatory effect of VEGF on endothelial proliferation, migration and permeability [18,231,236] , while ATP exploits TRPC3 to activate NF-κB and increase vascular cell adhesion molecule-1 expression [237] . TRPC3-driven NO synthesis and vasore- TRPV1 TRPV2 TRPV3 TRPV4 TRPV5 TRPV6 PCa/PNa and conductance (pS) [202] 10, 35-80 1-3, NM 12, 172 6, 90 > 100, 75 > 100, 40-70 Human coronary artery ECs [300] (+RT-PCR, WB, IHC) Human pulmonary artery ECs [415] +(RT-PCR) +(RT-PCR) +(RT-PCR) Human pulmonary microvascular ECs +(RT-PCR) Human cerebral microvascular ECs [272] +(RT-PCR, IC) Human cerebral arterioles ECs [305] +(RT-PCR, IHC) Human dermal microvascular ECs [319] +(RT-PCR, WB) Breast cancer derived microvascular ECs [319] +(RT-PCR, WB) Human umbilical vein ECs [227,277,296,301] +(RT-PCR) +(WB, IHC) Mouse aortic ECs [280,285,299,306] +(WB) +(RT-PCR, WB, NM, IHC) Mouse pulmonary artery ECs [313] +(WB, IHC) Mouse mesenteric artery ECs [27,280,302] +(RT-PCR, WB, IC) +(RT-PCR, IC) Mouse cerebral microvascular ECs +(RT-PCR) +(RT-PCR, WB) +(RT-PCR) Mouse dermal microvascular ECs [307] +(RT-PCR, WB) Mouse carotid artery ECs [290,296] +(IHC) Rat mesenteric artery ECs [226,275,302] +(WB) +(WB, IC, IHC) Rat femoral artery ECs [312] +(RT-PCR, IC) Rat pulmonary artery ECs [303] +(WB, IHC) Rat renal artery ECs [303] +(IHC) Rat cardiac microvascular ECs [303,…”
Section: A Drop In Luminal Camentioning
confidence: 99%
“…TRPV4: TRPV4 is the most polymodal TRP channel, being a molecular integrator of both chemical and physical stimuli [200,270] , and may be expressed in both native and cultured ECs (Table 3). More specifically, endothelial TRPV4 may be activated by non-noxious temperatures (> 24 ℃) [288] , hypo-osmotic cell swelling [289] , shear stress [290,291] , cyclic strain [292,293] , and pharmacologically, by the non-PKC-activating phorbol ester, 4α-phorbol-12,13-didecanoate (4αPDD) [294] and by the plant-derived flavone, apigenin [295] . Cell swelling and shear stress do not gate TRPV4 directly, but via the PLA2-dependent synthesis of AA, and its subsequent metabolization to 5',6'-epoxyeicosatrienoic acid (EET) through a CYP epoxygenase-dependent pathway [290,291,[296][297][298][299] .…”
Section: Trpv2mentioning
confidence: 99%
See 1 more Smart Citation
“…TRPV4 channels in the vascular ECs and SMCs are critically involved in the vasodilatation of mesenteric arteries in response to endothelial-derived factors [28]. One study found that the genetically encoded loss-of-function of trpv4 resulted in a loss of shear stress-induced vasodilatation, a response pattern largely dependent on endothelial TRPV4 expression [55]. In a previous study, we demonstrated that TRPM8 activation, by its agonist menthol, antagonized vasoconstriction by inhibiting Ca 2+ signaling-mediated RhoA/ROCK activation in the vasculature [56].…”
Section: Trp Channels Contribute To Vasodilatationmentioning
confidence: 99%
“…Ca 2+ entry through endothelial TRPV4 triggered NO-dependent vasodilation in rat conduit arteries, and NO-dependent and EDHF-dependent vasodilaton in small-sized A gracilis. Furthermore, shear stress induced vasodilation is significantly reduced in carotid arteries from TRPV4 knockout (-/-) mice [27].…”
Section: Trpv4mentioning
confidence: 99%